Radiographic evaluation of treatment by orthopedic procedures of mandibular fractures in Abidjan Odonto-stomatological consultation and treatment center - Kamon Jean-Claude N’cho; Kouassi Ange Patrick Kouassi; Giles Thierry Maroua (Indonesian Journal of Prosthodontic, 2025)
Introduction In Abidjan, mandibular fractures are generally treated surgically in the stomatology and maxillofacial surgery department of the Hospital and University Centers (HUC) of Cocody and Treichville. They are also treated with orthopedic devices at the Dental Surgery Consultation and Treatment Center in Abidjan, within the Maxillofacial Prosthesis (PMF) section of the Clinical Prosthesis and Occlusodontics department. Are these orthopedic devices effective in the management of mandibular fractures? Do these methods achieve satisfactory results in the management of mandibular fractures? Material and methods This is a retrospective descriptive analytical study based on the evaluation of usable clinical and radiographic files of patients admitted to the maxillofacial prosthesis section of Odonto-Stomatological Consultation and Treatment Center (CCTOS) who presented fractures to the mandible. The data was processed using epi data software and the search for correlations was carried out using the khi-deux test. Results Maxillo-mandibular restraint is the most used with a rate of 85%. 83% of patients have good bone density on radiography after healing. Conclusion Orthopedic treatment of mandibular fracture could be indicated in cases of non-displaced fracture with excellent alignment or approximation of bone fragments and some easily reducible fractures. Keywords: radiographic evaluation, orthopedic procedures, mandibular fractures